Insān Ilahī as The Main Concept of Mulla Sadra’s Transcendental Human Existences - Nurul Khair; Wa Ode Zainab Zilullah Toresano (NALAR, 2020)
This writing is library research on Mulla Sadra’s thought concerning the concept of insān ilahī as the main concept of transcendental existence discourse in response to western humanism paradigm because it consider vanishing the immaterial domain in human self. This writing is aimed to explain about perfection, happiness, and freedom as the value and main purpose of human existence in Islamic Philosophy civilization based on Mulla Sadra master piece al-Hikmah al-Mutāliyah fī al- Asfār al-Aqliyyah al-Arba’ah. By using descriptive-philosopical method we come to conclusion that the concept of insān ilahī in Mulla Sadra viewpoint were discussed and observed through transcendental discourse. Soul in Mulla Sadra view is immaterial substance which always went through the process of perfection in human existence. Besides knowing that there is immaterial substance in human existence, the concept of Mulla Sadra insān ilahī has also fix many falsity of western philosopher in describing the value and main purpose of man based on material awareness. The result is, individual viewing perfection and potential actualization in him depends on the things which based on logic to view the object of perception based upon his physical existence in reality. The dependence of existence toward material things describes the perfection which gained by individual partially. The result of this writing is to offer a new point of view in understanding the unlimited value and purpose of human existence toward particular paradigms through the concept of Mulla Sadra insān ilahī as the main concept of transcendental existence in Islamic Philosophical Civilization.Keyword: Existence, West, Islam